2020
DOI: 10.1128/jvi.00660-20
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-Mediated Neutralization Reveals an Achilles Heel for Norovirus

Abstract: Human norovirus frequently causes outbreaks of acute gastroenteritis. Although discovered more than five decades ago, antiviral development has, until recently, been hampered by the lack of a reliable human norovirus cell culture system. Nevertheless, a lot of pathogenesis studies were accomplished using murine norovirus (MNV), which can be grown routinely in cell culture. In this study, we analyzed a sizeable library of nanobodies that were raised against the murine norovirus virion with the main purpose of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…There are many different steps during the life cycle of pathogens in the body, including cell attachment and entry, replication and regulation, transcription and translation, and virion assembly, offering diverse targets (Koromyslova et al, 2020;Tsukuda and Watashi, 2020). Pathogens have low homology with humans, exhibiting a variety of attractive epitopes.…”
Section: Nanobody Targeting Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different steps during the life cycle of pathogens in the body, including cell attachment and entry, replication and regulation, transcription and translation, and virion assembly, offering diverse targets (Koromyslova et al, 2020;Tsukuda and Watashi, 2020). Pathogens have low homology with humans, exhibiting a variety of attractive epitopes.…”
Section: Nanobody Targeting Pathogensmentioning
confidence: 99%
“…Nanobodies that bind at a dimeric interface on the lower side of the P dimer disrupt a structural change in the capsid associated with binding cofactors. Furthermore, nanobodies induce conformational rearrangement of several P domain loops, leading to particle aggregation and interference at the HBGA binding pocket (Koromyslova and Hausman, 2018;Koromyslova et al, 2020). Kerstin Ruoff et al also demonstrated that nanobodies have different targets and inhibit norovirus infection through various mechanisms.…”
Section: Norovirusmentioning
confidence: 99%
“…Here we tested whether the accuracy of NanoNet Nb models is sufficient to enable sampling of the correct orientation. Docking was applied for 17 Nbs (7 Nbs that interact with SARS-CoV-2 spike RBD [20][21][22][23][24] , 2 Nbs that bind SARS-CoV-2 N protein 25 , 1 Nb binding to SARS-CoV-1 spike RBD, 1 Nb binding to the Ebola RNA methyltransferase 26 , and 4 MNV capsid protein P-domain Nbs 27 ). In addition, we docked two high affinity SARS-CoV-2 RBD Nbs (Nb21, Nb105) that bind to different epitopes 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This observation is surprising in the context of the previous literature, which would have better supported a role for specific P2 amino acids in mediating altered tropism and increased virulence. However, recent reports have suggested that norovirus capsid structures may be highly dynamic and that the P1 domain may govern this flexibility by regulating interactions with the shell domain [58][59][60][61][62]. We hypothesize that residue 514 may be involved in this flexibility, as several amino acids with which it is predicted to interact make up a portion of this flexible linker, in the capsids of both MNoV S7 (which possesses F514) and CW3 (which possesses I514) (S9 Fig) . F/I514 may influence this linker to adopt either the "expanded" or "closed" conformation, changing the capsid structure and altering its ability to interact with receptors and/ or the immune system.…”
Section: Plos Pathogensmentioning
confidence: 90%